Analisis Penegakan Hukum Lingkungan terhadap Pencemaran Sungai dan Dampaknya bagi Masyarakat: Studi Kasus Limbah PT Harapan Mulya di Sungai Citeureup, Bogor - Rayi Kharisma Rajib; Beatrice Mauren Delicia; Kamila Dzakiatuz Zahra (INDO PUBLISHING, 2026)
River pollution from industrial waste poses a serious threat to ecosystem sustainability and community welfare in the industrialisation era. This study aims to analyse the implementation of environmental law enforcement in the Citeureup River pollution case involving PT Harapan Mulya in Bogor Regency, as well as to assess its effectiveness and impact on surrounding communities. The research employs a normative juridical method with a qualitative and conceptual approach, focusing on secondary data such as laws, regulations, and scientific literature. The findings show that law enforcement has been carried out gradually through administrative measures by the Bogor Regency Environment Office, including site sealing and closure of waste channels (grouting) as forms of government coercion (bestuursdwang). There is also potential for criminal sanctions under Law Number 32 of 2009 through the principle of strict liability. The pollution has significantly degraded water quality, damaged aquatic ecosystems, and caused health problems and economic decline for residents relying on the river. The study concludes that although regulations are systematic, effective enforcement requires stronger supervision , better coordination, and greater compliance from business actors to ensure environmental protection and intergenerational justice